Using the Factor Theorem, it is found that:
a) [tex]f(x) = x^3 - 6x^2 + 9x - 4[/tex]
b) Due to equal lateral limits, there are no breaks in the domain of h(x).
[tex]f(x) = a(x - x_1)(x - x_2) \cdots (x - x_n)[/tex]
Item a:
The zeroes are:
Then:
[tex]f(x) = (x - 4)(x - 1)(x - 1)[/tex]
[tex]f(x) = (x - 4)(x^2 - 2x + 1)[/tex]
[tex]f(x) = x^3 - 6x^2 + 9x - 4[/tex]
Item b:
The piece-wise function is defined by:
[tex]h(x) = x^3 - 6x^2 + 9x - 4, x \leq 0[/tex]
[tex]h(x) = \sqrt[3]{x} - 4, x > 0[/tex]
Using lateral limits at the point in which the definition is changed:
[tex]\lim_{x \rightarrow 0^-} h(x) = \lim_{x \rightarrow 0} x^3 - 6x^2 + 9x - 4 = -4[/tex]
[tex]\lim_{x \rightarrow 0^+} h(x) = \lim_{x \rightarrow 0} \sqrt[3]{x} - 4 = -4[/tex]
Due to equal lateral limits, there are no breaks in the domain of h(x).
To learn more about the Factor Theorem, you can take a look at https://brainly.com/question/24380382